DECODING INDIA’S ECONOMIC REFORMS: A 30-YEAR REVIEW - Pillai, Seema (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The study "Decoding India’s Economic Reforms: A 30-Year Review" critically examines the evolution, impact, and outcomes of India’s economic reforms that began in 1991. These reforms marked a transformative phase in India’s economic landscape, from a closed, regulated economy to a liberalized, globalized one. This review covers the significant policy changes, their implications on various sectors such as agriculture, manufacturing, services, trade, and foreign investment. Through this, the paper aims to offer insights into how these reforms have shaped India’s economic growth, challenges, and the socio-economic structure over three decades.